The Sociological Prospect - Bottomore, Tom (Cahiers de recherche sociologique, 1990)
SummarySociology emerged as a new social science characterized by the coexistence of disparate and conflicting schemes of thought. Since two decades, very important work has been done to provide a more secure basis for sociological theories of the future. The paper presents an overview of various paradigms and gives a distinctive place to Marxism as a theory having produced major explanations still far from being surpassed. The future of the discipline is seen through a possible period of renewal which, it is hoped, is not too far away.